Fetal Lung-Derived Exosomes in Term Labor Amniotic Fluid Induce Amniotic Membrane Senescence - Wan, Shuting; Chen, Pengzheng; Gu, Mengqi; Liu, Jing; Zhou, Qian; Zhang, Fengyuan; Lu, Yuan; Li, Lei; Wang, Xietong (Frontiers in Cell and Developmental Biology, 2022)
The mechanism of parturition is still unclear. There is evidence showing that delivery is associated with amniotic membrane cellular senescence. We isolated fetal lung-associated exosomes from the amniotic fluid at term labor (TL-exos) and verified that the exosomes can cause primary human amniotic epithelial cell (hAEC) senescence and apoptosis and can release higher levels of senescence-associated secretory phenotypes (SASPs) and proinflammatory damage-associated molecular patterns (DAMPs) than exosomes isolated from the amniotic fluid at term not in labor (TNIL-exos). The human non-small-cell lung cancer cell line (A549) can be used as an alternative to alveolar type 2 epithelial cells producing pulmonary surfactant. Therefore, we isolated A549 cell-derived exosomes (A549-exos) and found that they can trigger hAECs to undergo the same aging process. Finally, the animal experiment suggested that A549-exos induced vaginal bleeding and preterm labor in pregnant mice. Therefore, we conclude that exosomes derived from fetal lungs in term labor amniotic fluid induce amniotic membrane senescence, which may provide new insight for explorations of the mechanism of delivery.